Poverty alleviation and health services for the poor in China: evidence from national health service surveys in 2013 and 2018 - Xiaoyun Liu; Mingyue Li; He Zhu; Qinqin Liu; Xueqin Xie (BMC, 2023)
Abstract Background China has made intensive efforts to eliminate extreme poverty by 2020. This paper aims to evaluate the changes in health service needs, utilization, and medical expenses for poor people during the poverty alleviation period. Methods The study used data from national health services surveys in 2013 and 2018. The poor people were identified and certified by the local government. Health service needs, utilization, medical expenses, and reimbursement rates were analyzed and compared between 2013 and 2018, between the poor and the non-poor groups. Results People living in poverty were usually elderly, illiterate, and unemployed. The poor people had a significantly higher two-week morbidity rate and a higher prevalence of chorionic non-communicable diseases than the non-poor group. For both the poor and non-poor, health service needs increased between 2013 and 2018. Accordingly, the poor people had more use of outpatient and inpatient services. The annual inpatient admission rates were 20.8% and 13.1% for the poor and non-poor, respectively, in 2018. The average medical expenses per inpatient admission were much lower for the poor than for the non-poor. Out-of-pocket (OOP) payment share decreased from 41.9% to 2013 to 31.9% in 2018 for the poor, while for the non-poor, the OOP rate was much higher (45.4%) and had no significant changes between the two surveys. The reduction in the OOP share occurred mostly in rural areas. Conclusions Poverty alleviation in China may have positive effect in improving poor people's access to health services, and reducing their financial burden due to illness and health service utilization.